2022
DOI: 10.3390/medicina58091205
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Traditional and in Motion Nd:YAG Laser in Hair Removal: A Prospective Study

Abstract: Background and Objectives: Hair removal is a common cosmetic problem interesting more and more patients nowadays. Various laser treatments are currently available. Alexandrite and Nd:YAG laser are the most effective procedures in lighter and darker skin phototypes, respectively. Materials and Methods: A total of 40 patients seeking hair removal in one or more body areas with skin phototypes 2–6 was recruited to perform this study. Patients were divided into two groups. One group was treated with the standard N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The side effects, such as sensitivity, erythema, hyperpigmentation, and burns, depend on the patient's skin phototype, on the device, and on the operator's expertise. It is well-known that laser hair reduction causes no long-term adverse effects [7] and currently underway studies are highlighting how the "in motion" use of laser sources such as long-pulsed Nd: YAG, albeit with the same efficacy compared to its standard use, has fewer side effects [8].…”
Section: Discussionmentioning
confidence: 99%
“…The side effects, such as sensitivity, erythema, hyperpigmentation, and burns, depend on the patient's skin phototype, on the device, and on the operator's expertise. It is well-known that laser hair reduction causes no long-term adverse effects [7] and currently underway studies are highlighting how the "in motion" use of laser sources such as long-pulsed Nd: YAG, albeit with the same efficacy compared to its standard use, has fewer side effects [8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that patients undergoing single-source laser treatment Ş. Gençoğlu experience greater pain during procedures [21]. Excessive pain can impede success.…”
Section: Discussionmentioning
confidence: 99%